An intensity comparison of light bulbs using spectroscopy method - S., Nurulain; N. O., Sharif; F., Siddiq; M. R., Salim; H., Manap (2020)
This paper describes the differences between light intensity of light bulbs from different working principle. A Maya2000 spectrometer from Ocean Optics is used as a light detector. The intensity of light is taken within the visible wavelength between 390 nm to 700 nm. It is observed that light intensity from different type of light bulbs forms different spectral power distribution. The light emitting diode (LED) lamp shown to be the most efficient light bulbs with the highest average light intensity compared to incandescent and fluorescent lamps.